REVITALISASI NILAI-NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI MASYARAKAT DESA HILIANAA - Fatolosa Hulu (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The revitalization of the values of Pancasila is an important effort to maintain the unity and integrity of the Indonesian nation, particularly at the village community level. This community service research aims to integrate and revive the values of Pancasila in the daily lives of the people of Hilianaa Village. The method employed is a participatory approach, involving various community elements in activities such as socialization, training, and discussions based on the principles of Pancasila. The expected outcome of these activities is to strengthen the community’s understanding of the relevance of Pancasila values in a socio-cultural context and to foster solidarity and mutual cooperation within the village. Additionally, the program seeks to raise public awareness of the importance of Pancasila values as a foundation for building a harmonious and democratic society.